2017
DOI: 10.1007/s12192-017-0808-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal treatment of luteolin-7-O-β-glucoside improves its immunomodulatory and antioxidant potencies

Abstract: Phytochemicals extracted from flowers, roots and bark, leaves, and other plant sources have been used extensively throughout human history with varying levels of efficacy in prevention and treatment of disease. Recently, advanced methods for characterization and clinical use of these materials have allowed modern understanding of their properties to be used as immunomodulatory agents that act by enhancement of endogenous cytoprotective mechanisms, avoiding interference with normal physiologic signaling and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 61 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…The content of flavonoid in the ethyl acetate with the maceration method is 38.36 ± 0.14 mg QE/g. 29,30 . The research showed that the extraction methods influence the yield percentage, the phenolic and flavonoid content of extract, and the antioxidant properties and antibacterial activity.…”
Section: Analysis Of Total Phenolic and Flavonoid Compoundsmentioning
confidence: 99%
“…The content of flavonoid in the ethyl acetate with the maceration method is 38.36 ± 0.14 mg QE/g. 29,30 . The research showed that the extraction methods influence the yield percentage, the phenolic and flavonoid content of extract, and the antioxidant properties and antibacterial activity.…”
Section: Analysis Of Total Phenolic and Flavonoid Compoundsmentioning
confidence: 99%
“…6,7 Clinical epidemiology study demonstrates that luteolin has various biological and pharmacological activities, such as antibacterial action, antiviral action, antioxidation activity, antitumor activity, hypoglycemic effect, hypolipidemic effect, hypotensive effect and immunomodulatory functions, etc. [8][9][10] In recent years, numerous researchers have found that luteolin has broad-spectrum antitumor activities with many different forms. By regulating intricate signal transduction pathways, luteolin presents multiple antineoplastic effects, such as antitumor cell proliferation, anticarcinogen effects, blocking cell cycle progression, inducing tumor cells apoptosis,inhibiting the infiltration and metastasis of tumor and the growth of new vessels, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 revealed that the oxidation of DCFH-DA by peroxyl radicals, derived from ABAP, was significantly reduced by heated NG, heated L7G and heated Erio, reaching 52.68%, 72.3% and 83.88%, respectively, at the highest tested concentrations. Heated molecules seem to be more efficient in protecting splenocytes against peroxyl radical-induced oxidation compared to native molecules (13.6%, 60%, and 46.5% respectively) [39,40,57]. These findings are confirmed by in vivo assay.…”
Section: Evolution Of the Biological Activities Of The Flavonoid Model Solutions Thermally Treatedmentioning
confidence: 52%
“…The antioxidant activities in vitro and in vivo were assessed from model solutions of flavonoids treated at a temperature of 130 • C during 2 h [39,40].…”
Section: Model Solutions Of Flavonoidsmentioning
confidence: 99%